2002
DOI: 10.1002/pst.15
|View full text |Cite
|
Sign up to set email alerts
|

Bioequivalence and the pharmaceutical industry

Abstract: Since the early 1990s, average bioequivalence (ABE) studies have served as the international regulatory standard for demonstrating that two formulations of drug product will provide the same therapeutic benefit and safety profile when used in the marketplace. Population (PBE) and individual (IBE) bioequivalence have been the subject of intense international debate since methods for their assessment were proposed in the late 1980s and since their use was proposed in United States Food and Drug Administration gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…They advise that this potential subject  formulation interaction is a concern and that a replicated crossover design can provide an assessment of this interaction. We made no evaluation of the relevance of subject  formulation interaction or of the performance of estimates of this interaction; for a thorough discussion of this topic we refer the reader to the papers of Patterson and Jones [3,6] and to the literature that they cite. However, our results show that, with regard to ABE assessment, the EM analysis model (our Model 3) performs better than a simpler model that does not account for this interaction (Model 1) and than one alternative model (Model 4) that accounts for this interaction in a different way.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They advise that this potential subject  formulation interaction is a concern and that a replicated crossover design can provide an assessment of this interaction. We made no evaluation of the relevance of subject  formulation interaction or of the performance of estimates of this interaction; for a thorough discussion of this topic we refer the reader to the papers of Patterson and Jones [3,6] and to the literature that they cite. However, our results show that, with regard to ABE assessment, the EM analysis model (our Model 3) performs better than a simpler model that does not account for this interaction (Model 1) and than one alternative model (Model 4) that accounts for this interaction in a different way.…”
Section: Discussionmentioning
confidence: 99%
“…CV=30% or more) and/or when the true mean ratio is assumed to fall within the equivalence limits, but to deviate from 100% by more than 10%. A recent review of much of the literature in the area of BE assessment can be found in [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situations with missing data at random, one traditional approach to estimation and inference for d is to model the data using restricted maximum likelihood (REML) [9]. Approaches to the REML modelling of data in such studies are described by Patterson and Jones [10]. Unconstrained REML procedures may yield estimates which are negative; furthermore, it is known that estimates of variance are model-dependent (see [10] for more details).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the two-one sided test (TOST) proposed by Shuirmann (1987) (FDA, 2001), two formulations are claimed to be bioequivalent when the 90% confidence intervals (CIs) of mean log (AUC) differences and log (Cmax) differences fall within the regulatory acceptance limits (log (0.8) to log (1.25)). The mean differences in log (AUC) or log (Cmax) between the test and the reference formulation represent the formulation effect, a key parameter in the ABE test (Patterson and Jones, 2002).…”
Section: Introductionmentioning
confidence: 99%